2021
DOI: 10.1186/s12884-021-04208-3
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive concerns and fear of cancer recurrence: a qualitative study of women’s experiences of the perinatal period after cancer

Abstract: Background Young female cancer survivors are at a disproportionate risk of suffering significant psychological distress following treatment, particularly fears of cancer recurrence (FCR). While previous research has established the robust relationship between FCR and family matters (e.g., family planning and motherhood), there is a paucity of information about how a history of cancer affects women’s psychological functioning throughout the perinatal period. The present investigation sought to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(41 citation statements)
references
References 56 publications
0
41
0
Order By: Relevance
“…According to the results of an Iranian qualitative study conducted to explore the psychological response of BC survivors, factors such as feeling incompetence, despair of life, and fear of disease recurrence had been the most common psychological reaction of BC survivors [32]. Based on the results of a qualitative study regarding the fertility concern of BC survivors during the perinatal period showed that due to the higher possibility of psychological distress among women with cancer, they need more information and valid resources about fertility and reproductive issues [33]. As well as another qualitative study regarding motherhood during or after BC diagnosis indicated that the experience of motherhood has led to the return of the sense of well-being among BC survivors, but they had severe fear regarding the likely effect of cancer treatment on their fetus growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of an Iranian qualitative study conducted to explore the psychological response of BC survivors, factors such as feeling incompetence, despair of life, and fear of disease recurrence had been the most common psychological reaction of BC survivors [32]. Based on the results of a qualitative study regarding the fertility concern of BC survivors during the perinatal period showed that due to the higher possibility of psychological distress among women with cancer, they need more information and valid resources about fertility and reproductive issues [33]. As well as another qualitative study regarding motherhood during or after BC diagnosis indicated that the experience of motherhood has led to the return of the sense of well-being among BC survivors, but they had severe fear regarding the likely effect of cancer treatment on their fetus growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…When a woman is diagnosed with cancer, she faces several conflicts, which are often not clarified by the multidisciplinary team, such as the fear of not being able to get pregnant, the adverse reactions of chemotherapy that will prevent her from carrying out her work activities and that will impact in their monthly family budget, in addition to the emotional damage, due to the loss of hair and breasts, which directly impact on female high spirits (Medeiros et al, 2019;Taberna et al, 2020;Facchin et al, 2021;Vanstone et al, 2021). In addition to these internal conflicts, there are those related to the health service, with continuous trips to the oncological treatment environment, changes in the daily routine and difficulty in accessing the necessary tests and treatment, often having to take the tests and buy medicines privately , compromising even more the monthly budget of the family (Luiza et al, 2016;Cabral et al, 2019;Alves et al, 2022;Ivama-Brummell et al, 2022).…”
Section: Considerations About Work and Income Of Women In Chemotherap...mentioning
confidence: 99%
“…"Dual perspectives: Unifying the distinctive experiences of men and women in facing fertility issues" Sub-sub-theme 1.1.1 Men We extracted the theme of men's fertility concerns from three academic articles, which revealed that men's worries about fertility issues span across physiological, psychological, and social dimensions. Specifically, this encompasses compromised fertility function on a physical level, 33,36,58 emotional distress where individuals may have confidence in preserving future fertility while simultaneously experiencing psychological anguish, 47,49,52,56 and potential societal and cultural challenges that could lead to a loss of male identity. 53,56 Another two articles 56,58 provided the theme of men's needs when facing fertility issues, with these men desiring professional advice.…”
Section: Review Findingsmentioning
confidence: 99%
“…42,44,54 Additionally, there is a desire for communication, support, and acquisition of diverse scientific reproductive knowledge. 34,45,53 These encompass a range of information needs, including but not limited to the requirement for expertise from health care professionals 36,[44][45][46] ; the necessity for scientifically valid fertility information 36,42,44 ; the demand for diverse sources of information support 42,44,45 ; the need for information regarding potential fertility loss 45,49 ; the absence of decision-making and fertility-related information 36,52,57,58 ; and matters concerning pregnancy post-chemotherapy and radiotherapy. 58 Strategies for dealing with fertility issues include accepting reality, 48,51 seeking support-medical, informational, family, and social, 42,43,50 changing bad lifestyle habits, 43,48 handling distress, 48,51,56 finding meaning, 47,48 maintaining hope while suffering, 33,56 and providing advice to health care providers.…”
Section: Review Findingsmentioning
confidence: 99%
See 1 more Smart Citation